Topic Modelling Berbasis Embedding pada Komentar YouTube - Muhabbab, Ahmad Zein Abid; Rizki, Rohmad Ali Fatur (Seminar Nasional Official Statistics, 2024)
The National Data Center is a vital infrastructure for the Indonesian government in processing, storing, and protecting public data. However, the ransomware attack on June 20, 2024, not only disrupted operations but also potentially damaged the government's reputation and public trust. This research analyzes public perceptions of the attack through YouTube comments using topic modeling techniques. The analysis aims to understand public views, develop more effective communication strategies, and help restore public trust. Various embedding models, such as BERT and FastText, were evaluated using Coherence Score (